Data acquisition variability using profilometry to produce accurate mean total volumetric wear and mean maximum wear depth measurements for the OHSU oral wear simulator. Issue 8 (August 2016) - Fleming, Garry J.P.; Reilly, Edward; Dowling, Adam H.; Addison, Owen
Abstract: Objective: To identify the minimum data acquisition variables in the x - and y -planes required when using three-dimensional (3D) profilometry to produce accurate mean total volumetric wear and mean maximum wear depth measurements for a range of wear facets produced by an oral wear simulator. Methods: The Oregon Health Science University (OHSU) oral wear simulator was employed to wear an experimental resin-based composite formulation from 25, 000 to 400, 000 wear cycles. Mean total volumetric wear and mean maximum wear depth were determined using a contact profilometry at a measurement speed of 1 mm/s. An area (8 mm length and 4 mm width) was profiled on each wear facet comprising 8001 horizontal traces ( y -axis at 1 μm intervals) with 4001 measurement points ( x -axis at 1 μm intervals) resulting in 32, 012, 001 measurement points with a z -axis resolution of 40 nm. The minimum x - and y -axis spacing data acquisition requirement were assessed using the TalyMap software by reducing the number of measurement points in the original scanned wear facets and normalized data were converted to percentage values. Results: Minimum x - and y -axis spacing to achieve an accuracy of 99, 95 and 90% of the mean total volumetric wear value for the wear facets produced (25, 000–400, 000 wear cycles) were 20 μm × 20 μm, 100 μm × 100 μm and 200 μm × 200 μm, respectively but for maximum wear depth data normalized with respect to the 'true value or gold standard' the x - and y -axis spacing requirement varied with the size of the wear facet. Significance: The study emphasizes the difficulty in employing mean maximum wear depth measurements when assessing the in vitro wear facets produced by an OHSU oral wear simulator and accurate quantification of the mean total volumetric wear of a wear facet is a prerequisite to informing the profession about dental restorative wear performance.